1995
DOI: 10.1088/0964-1726/4/1a/013
|View full text |Cite
|
Sign up to set email alerts
|

Performance of embedded short-gage-length optical fiber sensors in a fatigue-loaded reinforced concrete specimen

Abstract: This paper reports the performance of short-gage-length optical fiber sensors embedded in a reinforced concrete specimen. Embedded extrinsic Fabry-Perot optical fiber sensors, attached to steel reinforcement rods, were used to monitor local displacements and strain in a concrete cross-beam specimen. The strain data obtained from the fider sensors were compared with data obtained from collocated foil strain gages. Absolute extrinsic Fabry-Perot interferometric sensors, capable of measuring absolute displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…De Vires et al [7] reported that Fabry-Perot FOS output signals compared well with the output signals obtained from collocated strain gauge in the test of a concrete cross-beam specimen, and FOS had a much better signal-to-noise ratio than the strain gauge. Quirion and Ballivy [8,9] have evaluated the performance of the Fabry-Perot FOS when it was embedded in concrete cylinders.…”
Section: Monitoring Of Strain and Displacementmentioning
confidence: 93%
“…De Vires et al [7] reported that Fabry-Perot FOS output signals compared well with the output signals obtained from collocated strain gauge in the test of a concrete cross-beam specimen, and FOS had a much better signal-to-noise ratio than the strain gauge. Quirion and Ballivy [8,9] have evaluated the performance of the Fabry-Perot FOS when it was embedded in concrete cylinders.…”
Section: Monitoring Of Strain and Displacementmentioning
confidence: 93%
“…The round trip phase of the beam can be shown to be in the form of: nl 4 (1) where n in the index of refraction, is the optical wavelength, and l is the length of the cavity [14]. The ratio of reflected power to incident power is related to the round trip phase difference and the reflecting coefficient: (2) where R 1 and R 2 are the power reflection coefficients, and A is the cavity losses [10]. The strain on the FPI as a result of external parameters is given by:…”
Section: Efpi Sensor and Sinusoidal Strainmentioning
confidence: 99%
“…At low strain levels, the Fabry-Perot strain sensors have a linear strain to output intensity ratio. However, at high strain levels, they are very non-linear, requiring special demodulation schemes such as fringe counting, phase counting, and white-light interferometery [9,10,11,12]. In this work, a method employing the harmonics of an Extrinsic Fabry-Perot Interferometric (EFPI) signal as calibration points will be described.…”
Section: Introductionmentioning
confidence: 99%
“…Recent employment of a fiber optic sensors included embedding fiber optic sensors into concrete superstructure for civil application to measure vibration intensities, wind pressure, temperature, stress/strain sensing, and general building health monitoring [8,9]. Another application includes using fiber optic sensors on railway bridge and scale model bridge element [8,10,11].…”
Section: Introductionmentioning
confidence: 99%